2019
DOI: 10.1002/mc.23118
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucocorticoid signaling in urothelial tumorigenesis: Inhibition by prednisone presumably through inducing glucocorticoid receptor transrepression

Abstract: Glucocorticoids, including dexamethasone (DEX) and prednisone (PRED), have been prescribed in patients with neoplastic disease as cytotoxic agents or comedications. Nonetheless, it remains uncertain whether they have an impact on the development of bladder cancer. We, therefore, assessed the functional role of the glucocorticoid‐mediated glucocorticoid receptor (GR) signaling in urothelial tumorigenesis. Tumor formation was significantly delayed in xenograft‐bearing mice with implantation of control bladder ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Suppression of NF-κB transactivation thus represents an indirect mechanism of glucocorticoid action referred to as GR transrepression. As described above, GR transrepression induced by prednisone [50] and CpdA [52] is associated with the prevention of urothelial tumorigenesis.…”
Section: Nf-κbmentioning
confidence: 74%
See 1 more Smart Citation
“…Suppression of NF-κB transactivation thus represents an indirect mechanism of glucocorticoid action referred to as GR transrepression. As described above, GR transrepression induced by prednisone [50] and CpdA [52] is associated with the prevention of urothelial tumorigenesis.…”
Section: Nf-κbmentioning
confidence: 74%
“…Meanwhile, it has been documented that prolonged systemic use of glucocorticoids use was at an increased risk of developing bladder cancer [49], presumably due to associated immune suppression. Our recent studies using the in vitro transformation system described above demonstrated that GR knockdown in SVHUC cells resulted in the significant prevention of MCA-induced neoplastic transformation of urothelial cells [50]. More interestingly, of a total of 11 glucocorticoids screened including dexamethasone, only prednisone significantly inhibited the neoplastic transformation of urothelial cells.…”
Section: Grmentioning
confidence: 92%
“…Next, we tried to explore its comprehensive effects in the BCa patients, and found that the expression levels of GR were lower in bladder tumors compared with bladder non-neoplastic tissue and in high-grade/MI tumors compared with low-grade/NMI tumors (28). Finally, we compared the inhibitory effects of 11 GR ligands, and found that prednisone significantly suppressed their neoplastic transformation (29). Previous studies indicated that GR might be a tumor-suppressor gene in the BCa, but the internal cause has been unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study demonstrated that prolonged use of glucocorticoids was associated with an elevated incidence of bladder cancer (50), presumably via immunosuppression. By contrast, our recent study has revealed that a synthetic glucocorticoid prednisone prevents the malignant transformation of GR-positive urothelial cells, but not that of GR-negative cells (51). Prednisone and other natural or synthetic glucocorticoids, such as corticosterone and dexamethasone, have also shown to strongly inhibit bladder cancer cell invasion and metastasis via, for instance, inactivating NF-κB (52-54).…”
Section: It Remains Controversial Whether Glucocorticoids Induce Versus Inhibit Urothelial Tumorigenesismentioning
confidence: 96%
“…Apart from glucocorticoid-induced immunosuppression, glucocorticoid-mediated GR signals appear to have dual roles (i.e., inhibition of tumor development and progression versus promotion of cell proliferation) in urothelial cancer. Further studies have indicated that the action of glucocorticoids may be dependent on a balance between transactivation and transrepression of GR ( 51 , 54 , 55 ) that involve their therapeutic effects and associated adverse effects, respectively. In particular, transrepression appears to correlate with the function of GR as a tumor suppressor.…”
Section: Grmentioning
confidence: 99%